Pentingnya Tracer Sebagai Kartu Pelacak Berkas Rekam Medis Keluar dari Rak Penyimpanan - Savitri Citra Budi (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2015)
The availability of medical record quickly and accurately when needed will greatly help the quality of health care provided to patients. If the medical record filing system were poor then there will be problems that can interfere with the availability of medical record. In the case of medical record filing system, the staffs at Dlingo I Bantul community health center do not using tracer to mark the medical records that were out from storage. This will have an impact on the wrong location, misfile, and complicates the return of medical record in the right order. Method used in this community service was the diffusion of science and technology to design the tracer which is suitable for use in Dlingo I Bantul community health centers. Furthermore, the training was also implemented, started with counseling. Community service was running smoothly. At first, the tracer was not used as a tracker and a guidance of medical record which was out from the storage. After counseling and training, the staffs finally realized that it is necessary to use tracer.